ANALISIS PSIKOLOGI TERHADAP KONFLIK BATIN TOKOH MUFTI DALAM NOVEL DIKEJAR BAYANGAN KARYA DJAWASTIN HASUGIAN - Sari, Fitria Karmila; Rudyprasasti, Yoshinta Aprila (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2020)
Literary works are part of works commonly referred to as works of fiction that have links to topics that support life. A writer is free to pour pleasure and live it into fiction. This Beneficial Object uses the novel Chased by Shadow by Djawastin Hasugian. The novel